The metabolism of glucocerebrosides - From 1965 to the present. - Futerman, A; Platt, F (Elsevier, 2016)
Gaucher disease is caused by the defective catabolism of the simple glycosphingolipid, glucosylceramide (GlcCer), due to mutations in the GBA1 gene which encodes for acidβ-glucosidase (GCase), the lysosomal enzyme that degrades GlcCer. Today, Gaucher disease patients are routinely treated with recombinant GCase, in a treatment regimen known as enzyme replacement therapy (ERT). We now review the biochemical basis of ERT and discuss how this treatment has advanced since it was first pioneered by Dr. Roscoe Brady in the 1960s. We will place particular emphasis on the three dimensional structure of GCase, and subsequently discuss a relatively new treatment paradigm, substrate reduction therapy (SRT), in which GlcCer synthesis is partially inhibited, thus reducing its accumulation. Both of these approaches are based on studies and concepts developed by Dr. Brady over his remarkable research career spanning six decades.